Law Enforcement Against Children Who Are Narcotics Traffickers Based on the Influence of the Family Environment Linked to Article 55 Paragraph (1) of the Criminal Code Concerning Inclusion - Muhammad Adil MA (Publikasi Indonesia, 2025)
Drug crimes remain a major problem, and their existence is still being combated. The main problem in this research is the weak application of Article 55 paragraph (1) of the Criminal Code in cases involving children involved in drug trafficking due to family influence. Adult perpetrators who instruct or exploit children often escape prosecution. The purpose of this research is to analyze the forms of law enforcement against child drug traffickers influenced by family influence, explain the reasons for the non-implementation of Article 55 paragraph (1) of the Criminal Code in cases involving children and parents, and identify obstacles faced by law enforcement officials in Riau Province. This research can be classified as sociological juridical research. The research location is in Riau Province, specifically within the jurisdiction of the Bangkinang District Court, the Pekanbaru District Court, the Kampar District Prosecutor's Office, and the Pekanbaru District Prosecutor's Office. The population and sample comprises all parties related to the problem under study. This study used primary and secondary data sources, and data collection was conducted through interviews.